Introduction of ICT subject in Zanzibar primary education: Challenges and opportunities - Abubakar Diwani Bakari; Msellem Mohammed Ali (Social Sciences and Humanities Open, 2023)
This study was intended to examine the challenges and opportunities of ICT subject teachers in teaching ICT subjects to primary school students. The study was meant to answer the following questions: What are the challenges of implementing ICT in education policy and in introducing ICT subjects in Zanzibar's primary schools? What opportunities arise in the introduction of ICT subjects in Zanzibar's primary schools? This quantitative study used questionnaires to collect data from 73 primary school ICT teachers who were selected from 44 schools. Four schools were randomly selected from each of the 11 districts of Zanzibar, Tanzania. Quantitative data was analyzed through descriptive analysis whereby percentages and statistical measures were employed. The study found that 80% of the teachers had positive perceptions of the importance of ICT subjects in primary school. The results showed that challenges were based on the insufficiencies of ICT facilities, teachers' knowledge, and technological support in most primary schools. However, the study revealed that the positive attitudes of the teachers engendered the opportunities for the introduction of ICT subjects in Zanzibar's primary schools. This study recommended effective implementation of ICT subjects in schools through employing qualified ICT graduates. In addition, teachers should be well-equipped with ICT teaching methodologies and ICT practical skills. Also, the Ministry of Education should cover the existing gap of knowledgeable teachers in the ICT field as well as equip ICT facilities in schools.